Railway engineer N.L. Shchukin: life and activities - Povyssha, M. A. (History of science and technology, 2013)
In this article presents life and activity of Nikolay Shchukin, remarkable blighty personality. Shown his contribution to scientific, pedagogical and engineering activity. Nikolay Shchukin is an author a lot of textbooks, including theoretical mechanics (statics, kinematics, dynamics and hydraulics, monograph on lokomotie bilding. His pedagogical activity was marked electing the honoured member of the Technological institute and Military Engineering academy. We selected four directions in engineering activity of Nikolay Shchukin: creation of more powerfull lokomotives, creation of powerful factory on repair of locomotives, introductions of normalization and standardization on a transport, introductions of more perfect coupling of lokomotives. He created a powerful locomotive «Schuka».